Photopolymerization kinetics and dynamic mechanical properties of silanes hydrolysed without evolution of byproducts. Tetrakis(methacryloyloxyethoxy)silane - diethylene glycol dimethacrylate - Uygun, Mustafa (2011)
The temperature dependence of photopolymerization kinetics of tetrakis[(methacryloyloxy)ethoxy]silane (TetMESi) was compared with an analogue, diethylene glycol dimethacrylate and their copolymers. In all cases, the kinetics are controlled by the temperature dependence of the propagation step, the effect of diffusion on radical termination, the effect of rising glass transition during cure, and topological restraint on complete conversion. The glass transition regions of these polymers were very broad, suggesting their use in high temperature applications. NMR of the TetMESi monomer, and FTIR and water sorption measurements during exposure to water of the TetMESi-based polymers showed that the Si−O−C bond was slowly hydrolyzed, resulting in water-swollen polymers containing poly(hydroxyethyl methacrylate) which reduced the glass transition temperature and narrowed the glass transition region. UV−vis spectroscopic studies showed that during exposure to water, SiO2 nanoparticles or nanostructures were formed from the condensation of the silanol groups formed during the hydrolysis of TetMESi.